Dominance of Workers' Rights in the Profit Sharing System (Mukhabarah) Based on the Principle of Balance - Yustiloviani; Farida Arianti; Maisarah Leli; Riri Syafitri (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research is based on the requirement to do work that is not in line with the obligation to provide capital, the system of difficulties at the work level needs to be discussed in an obligation that will be fulfilled. In line with this, to increase understanding of workers' rights in agricultural cooperation with a profit sharing system based on the principle of balance when linked to the level of difficulty of the work. This study aims to analyse the forms of rights and obligations in the palm sap processing cooperation, and how the profit sharing of the mukhabarah system is based on the principle of balance. This research is empirical legal research based on a qualitative descriptive with phenomenology. In data collection, researchers conducted interviews with research informants based on interview guidelines. This research was conducted in Nagari Supayang, Tanah Datar Regency, West Sumatra.The results of the study indicate that there is a heavier burden and greater risk to the manager. The work of managing palm sap requires more days, both climbing days and days of processing palm sap. The conclusion is that there is a dominance of workers' rights in profit sharing agricultural cooperation based on the principle of balance where workers get their rights based on the magnitude of the work responsibilities they carry.Keywords: Balance, Mudharabah, Mukhabarah, Profit Sharing, Workers' Rights. AbstrakPenelitian ini dilatarbelakangi oleh adanya kewajiban untuk melakukan pekerjaan yang tidak sejalan dengan kewajiban memberikan modal, maka sistem yang berkaitan dengan kesulitan pada pekerjaan perlu dibahas terutama terkait kewajiban tertentu yang akan dipenuhi. Sejalan dengan hal tersebut, penelitian ini ditujukan untuk meningkatkan pemahaman tentang hak-hak pekerja dalam koperasi pertanian dengan sistem bagi hasil berdasarkan asas keseimbangan apabila dikaitkan dengan tingkat kesulitan pekerjaan. Penelitian ini bertujuan untuk menganalisis bentuk-bentuk hak dan kewajiban dalam koperasi pengolahan nira aren, dan bagaimana pembagian hasil sistem mukhabarah berdasarkan asas keseimbangan. Penelitian ini adalah penelitian hukum empiris berbasis metode deskriptif kualitatif dengan fenomenologi. Dalam pengumpulan data, peneliti melakukan wawancara dengan informan penelitian berdasarkan pedoman wawancara. Penelitian ini dilaksanakan di Nagari Supayang, Kabupaten Tanah Datar, Sumatera Barat. Hasil penelitian menunjukkan bahwa terdapat beban yang lebih berat dan risiko yang lebih besar bagi pengelola. Pekerjaan pengelolaan nira aren membutuhkan hari yang lebih banyak untuk menyelesaikan pekerjaannya, baik hari untuk pendakian maupun hari untuk pengolahan nira aren. Kesimpulannya adalah terdapat dominasi hak pekerja dalam kerjasama pertanian bagi hasil berdasarkan asas keseimbangan dimana pekerja mendapatkan haknya berdasarkan besarnya tanggung jawab pekerjaan yang diembannya.Kata kunci: Bagi Hasil, Hak Pekerja, Keseimbangan, Mudharabah, Mukhabarah.